Multinuclear Metal-Binding Ability of the N-Terminal Region of Human Copper Transporter Ctr1: Dependence Upon pH and Metal Oxidation State - Nardella, Maria Incoronata; Fortino, Mariagrazia; Barbanente, Alessandra; Natile, Giovanni; Pietropaolo, Adriana; Arnesano, Fabio (Frontiers in Molecular Biosciences, 2022)
The 14mer peptide corresponding to the N-terminal region of human copper transporter Ctr1 was used to investigate the intricate mechanism of metal binding to this plasma membrane permease responsible for copper import in eukaryotic cells. The peptide contains a high-affinity ATCUN Cu(II)/Ni(II)-selective motif, a methionine-only MxMxxM Cu(I)/Ag(I)-selective motif and a double histidine HH(M) motif, which can bind both Cu(II) and Cu(I)/Ag(I) ions. Using a combination of NMR spectroscopy and electrospray mass spectrometry, clear evidence was gained that the Ctr1 peptide, at neutral pH, can bind one or two metal ions in the same or different oxidation states. Addition of ascorbate to a neutral solution containing Ctr1(1-14) and Cu(II) in 1:1 ratio does not cause an appreciable reduction of Cu(II) to Cu(I), which is indicative of a tight binding of Cu(II) to the ATCUN motif. However, by lowering the pH to 3.5, the Cu(II) detaches from the peptide and becomes susceptible to reduction to Cu(I) by ascorbate. It is noteworthy that at low pH, unlike Cu(II), Cu(I) stably binds to methionines of the peptide. This redox reaction can take place in the lumen of acidic organelles after Ctr1 internalization. Unlike Ctr1(1-14)-Cu(II), bimetallic Ctr1(1-14)-2Cu(II) is susceptible to partial reduction by ascorbate at neutral pH, which is indicative of a lower binding affinity of the second Cu(II) ion. The reduced copper remains bound to the peptide, most likely to the HH(M) motif. By lowering the pH to 3.5, Cu(I) shifts from HH(M) to methionine-only coordination, an indication that only the pH-insensitive methionine motif is competent for metal binding at low pH. The easy interconversion of monovalent cations between different coordination modes was supported by DFT calculations.